2011
DOI: 10.1136/gutjnl-2011-300756
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered mouse models of pancreatic cancer: unravelling tumour biology and progressing translational oncology

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a devastating disease despite tremendous scientific efforts. Numerous trials have failed to improve the outcome on this deadliest of all major cancers. Potential causes include a still insufficient understanding of key features of this cancer and imperfect preclinical models for identification of active agents and mechanisms of therapeutic responses and resistance. Modern genetically engineered mouse models of PDAC faithfully recapitulate the genetic and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 67 publications
0
94
2
Order By: Relevance
“…Modeling these hallmark characteristics of PDAC in vivo using xenograft models has been largely disappointing, while genetically engineered mouse models (GEMM) based on pancreas-specific activation of oncogenic mutant Kras faithfully recapitulate the morphologic and molecular characteristics of human PDAC enabling sophisticated preclinical approaches (reviewed in ref. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling these hallmark characteristics of PDAC in vivo using xenograft models has been largely disappointing, while genetically engineered mouse models (GEMM) based on pancreas-specific activation of oncogenic mutant Kras faithfully recapitulate the morphologic and molecular characteristics of human PDAC enabling sophisticated preclinical approaches (reviewed in ref. 2).…”
Section: Introductionmentioning
confidence: 99%
“…p16/CDKN2A gene alteration is also an early genetic event found in PanIN-1 and PanIN-2, while the higher grade PanIN-3 lesions and invasive adenocarcinoma often harbor additional mutations in TP53, BRCA2, and TGFβ/SMAD4 pathway genes (Hruban et al, 2000;Kanda et al, 2012). Genetically engineered PDAC mouse models consistently recapitulate this genetic and biological evolution (Mazur & Siveke, 2012;Morris et al, 2010). In addition, whole-exome sequencing studies revealed that mutations in DNA damage response genes are prevalent in both PanIN and PDAC and that genes encoding proteins involved in gap junctions, actin cytoskeleton, mitogen-activated protein kinase (MAPK) signaling pathway, axon guidance, and cell-cycle regulation are among the earliest targets of mutagenesis in PanIN that progress to PDAC (Murphy et al, 2013).…”
Section: Precancerous Lesions: Pancreatic Intraepithelial Neoplasia mentioning
confidence: 90%
“…through the process of acinar to ductal metaplasia followed by malignant transformation (Hezel et al 2006, Mazur & Siveke 2012. Exocrine cells are in the vicinity of the islets of Langerhans and are thus directly exposed to high insulin concentrations.…”
Section: How Do Igf and The Insulin Systems Cooperate And Collaboratementioning
confidence: 99%
“…Though of low incidence, late detection and lack of effective chemotherapies make this cancer one of the deadliest, with a 5-year overall survival rate lower than 5% (Li et al 2004, Jemal et al 2008. In the last decade, substantial research efforts in investigating pancreatic carcinogenesis have broadened our knowledge and many molecular mechanisms essential for PDAC carcinogenesis and its maintenance have been described (Hingorani et al 2005, Siveke & Schmid 2005, Izeradjene et al 2007, Mazur & Siveke 2012. Still, efficient therapies are missing and targeted approaches have been largely disappointing.…”
mentioning
confidence: 99%